2015
DOI: 10.4236/ajps.2015.611175
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Achene Yield and Yield Related Traits of Sunflower Hybrids through Boron Application Strategies

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
2
2
0
1
Order By: Relevance
“…This might be due to the stimulatory effect of boron on sunflower and in enhancing metabolic process, pollen germination and improving development of pollen tube. These results also coincide with the findings of Shekhawat and Shivay (2008) and Imran khan et al, (2015). They reported that number of filled seeds/head and number of achenes/head were increased with boron application because of augmentation in pollen-production capacity of anthesis and pollen grain viability.…”
Section: Effect Of Management On Yield and Yield Attributes Of Sunflowersupporting
confidence: 91%
“…This might be due to the stimulatory effect of boron on sunflower and in enhancing metabolic process, pollen germination and improving development of pollen tube. These results also coincide with the findings of Shekhawat and Shivay (2008) and Imran khan et al, (2015). They reported that number of filled seeds/head and number of achenes/head were increased with boron application because of augmentation in pollen-production capacity of anthesis and pollen grain viability.…”
Section: Effect Of Management On Yield and Yield Attributes Of Sunflowersupporting
confidence: 91%
“…Whereas minimum stem diameter (l .66 cm) was recorded in plots where zinc was applied at 30 kg ha -1 which was statistically at par with Zn @ 0 and 10 kg ha -1 . These results matched with the investigations of Khan et al (2015) who stated that cell enlargement in growing tissues affected due to the deficiency of boron and it was involved in cell structure hence reduced stem diameter. The interaction between different levels of zinc and boron on stem diameter was also significant.…”
Section: Stem Diameter (Cm)supporting
confidence: 90%
“…Cultivar Helio251 was the most sensitive to variations of B availability, because its productivity was greater with the highest B doses (5 and 8 kg ha -1 ) than with the other doses (Figure 1B). Khan et al (2015) also found a beneficial effect of applying B on the grain production of sunflower hybrids (Patron 551 and S-278).…”
Section: Analysis Of Boronmentioning
confidence: 88%